-The 2030 Vision Saudi Graduates and the Challenges of Establishment Small Enterprises – A Case Study: Selected Saudi Universities - Alkasabh, Firas Ezzat Aklah (Journal of Economic, Administrative and Legal Sciences, 2019)
This study aimed at identifying the challenges facing the establishment of small pilot projects for Saudi universities’ graduates. This study examined the challenges as an independent variable that results in several dimensions (finance, technical capabilities, skills, administrative procedures and regulatory laws) and their effect on the establishment of small pilot projects in Saudi Arabia as a dependent variable. The researcher used a questionnaire survey to elicit data from the participants in which SPSS program was used to analyze and test the findings of the study. The participants of the study consisted of 416 Saudi graduates. This study concluded a number of findings including the following: • The amount of funds provided by MFIs to finance small projects is insufficient in which MFIs tighten their demand for guarantees and high loan interest rates. • The difficulty of the administrative procedures used in establishing small pilot projects. • The lack of technical capabilities and skills required for Saudi universities’ graduates, which reduces their ability to establish small pilot projects. Based on the findings of the study, the researcher recommended the need to provide sufficient funding for the establishment of small pilot projects with little interest and appropriate guarantees. Also, this study recommended the activation of the government’s role in guaranteeing small projects’ loans by a specialized institution. Further, the study recommended the need for launching governmental institutions to facilitate the procedures followed by establishing small pilot projects and preparing Saudi graduates through training and curriculum development to improve their skills and abilities.